MENAKAR PEMAAFAN PADA PENYINTAS CYBERBULLYING - Imam Setyawan (Jurnal EMPATI, 2023)
The purpose of this study is to see an overview of cyberbullying survivors' forgiveness in post-pandemic life. This research uses a quantitative descriptive approach. The research subjects were obtained through a purposive sampling technique, with characteristics, students who are cyberbullying survivors, with an age range of 18-21 years. Screening is carried out with a cyberbullying questionnaire containing questions related to self-identity, types of cyberbullying (based on Willard's theory namely, flaming, harassment, denigration, impersonation, outing & trickery, exclusion, and cyberstalking), repeated experiences of cyberbullying, and perpetrators of cyberbullying, to ensure that the subject is truly are truly survivors of one or more types of cyberbullying. The research subjects were 109 students who were obtained from the screening results and statements of willingness. Data collection uses a scale of forgiveness (25 items, α =   .931). Data analysis was performed using the Statistical Packages for Social Sciences (SPSS) version 26.0 program. The results showed that the subject's forgiveness was in the medium category, with a total of 62 people (57%), and the empirical mean was 58.16, within the medium category range (50 – 75). These results indicate that the forgiveness of cyberbullying survivors is not optimal, there are still 32 people (29%), in the low category. This condition occurs because most of the subjects are dealing with more than one type of cyberbullying, as well as the anonymity factor of the perpetrators of cyberbullying, most of whom come from strangers. No significant differences were found between male and female survivors' forgiveness.